2021
DOI: 10.1002/jbio.202100269
|View full text |Cite
|
Sign up to set email alerts
|

Study of the spatial scale stability of Mueller matrix parameters for textural characterization of biological tissues

Abstract: Mueller matrix imaging polarimetry (MMIP) is a promising technique for the textural characterization of biological tissue structures. To reveal the influence of imaging magnification on the robustness of Mueller matrix parameters (MMPs), the spatial scale stability of MMPs was studied. We established a new MMIP detector and derived the mathematical model of the spatial scale stability of MMPs. The biological tissues with well‐defined structural components were imaged under different magnifications. Then, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…When applied to clinical detection, the imaging speed should be considered in addition to the impact of imaging resolution. Some recent researches have shown that the polarization imaging method can better preserve the microstructural information of the sample when imaging resolution decreased compared to unpolarized optical imaging methods ( Shen et al, 2020 ; Liu et al, 2021 ; Chen et al, 2022 ; Yao et al, 2022 ). It indicates that adopting the polarization imaging method can well balance the requirements of imaging resolution and FOV, to acquire the micro- and even nanostructural ( Dong et al, 2020 ; Chen et al, 2021a ; Wang et al, 2021 ; Fang et al, 2022 ) properties of the scattering medium quickly using a relatively low NA objective.…”
Section: Introductionmentioning
confidence: 99%
“…When applied to clinical detection, the imaging speed should be considered in addition to the impact of imaging resolution. Some recent researches have shown that the polarization imaging method can better preserve the microstructural information of the sample when imaging resolution decreased compared to unpolarized optical imaging methods ( Shen et al, 2020 ; Liu et al, 2021 ; Chen et al, 2022 ; Yao et al, 2022 ). It indicates that adopting the polarization imaging method can well balance the requirements of imaging resolution and FOV, to acquire the micro- and even nanostructural ( Dong et al, 2020 ; Chen et al, 2021a ; Wang et al, 2021 ; Fang et al, 2022 ) properties of the scattering medium quickly using a relatively low NA objective.…”
Section: Introductionmentioning
confidence: 99%
“…During each stretch, the incident light generated by PSG illuminates the sample, and the light exiting from the sample passes through the PSA and is collected by the cameras. The final MMPs images are calculated from 24 images acquired with different combinations of PSG and PSA [ 36 , 37 ]. We have calibrated the inversion error of the Mueller matrix under the condition that the incident light was generated manually, and the average root mean square error of the air Mueller matrix was 0.0265.…”
Section: Methodsmentioning
confidence: 99%
“…For some clinical applications, imaging speed and resolution are both the key considerations. Recently, studies have shown that some polarization information obtained from Mueller matrix connecting with structural features can be preserved under relatively low imaging resolution [21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%